The mediating influence of marketing capabilities on the relationship between knowledge management and organization performance in hotel industry - Mohammed, Abdul Alem; Rashid, Basri; Tahir, Shaharuddin (IDOSI Publications, 2014)
Knowledge management (KM) is one of the main sources of competitive advantage for organizations.However the influence of KM on organization performance in hotel industry has received less attention.In addition, previous studies found inconsistent results regarding the influence of KM on organization performance. Therefore, this empirical study examines the influence of KM on hotel performance dimensions (financial, customer, internal process and learning and growth) in Malaysia.It also investigates the mediating effect of marketing capabilities (planning and implementation) on the relationship between KM and hotel performance. Data was collected using the survey method and 152 usable questionnaires were received from hotel managers.Regression analysis was conducted to test the relationships among KM, marketing capabilities and hotel performance.The results show a positive relationship between KM and hotel performance.They also indicate that marketing capabilities play a mediating role on the relationship between KM and hotel performance.The study suggests that KM is a main source of influence on marketing capabilities and hotel performance.By understanding the relationship among the constructs in the research model, hotel managers could maximize the utilization of their internal resources to improve organizational performance.